The effects of altitude training on erythropoietic response and hematological variables in elite endurance athletes - Fan, Y.; Gao, W.; Xiao, Z. (Exercise Biochemistry Review, 2018)
Objective To increase the capacity of blood oxygen-carrying of the endurance performance in athletes is the goal of altitude training. The key factor in the achievement of enhanced hematological variables is the stimulation in the hypoxia condition. Reticulocyte celles is the earliest red blood cells released to the bloods, it to be matured about 4days in the marrow. There are lots of research in the clinic tested reticulocyte can be monitor the change of the bone marrow hematopoietic system. The purpose of this study was to find out the effect of altitude training on reticulocyte indices of elite endurance athletes, further to analyzes the kinetics of erythropoiesis and hematological variables during and after altitude training.